Effect of a hydrogen peroxide gas-plasma sterilization on physical integrity and quality of N95 respirators: An experimental study during the COVID-19 pandemic - Malathi Murugesan; Sneha Radha; Bhagteshwar Singh; Prasad Mathews; Suresh Devasahayam; Priscilla Rupali (Current Medical Issues, 2022)
Background: N95 respirators have prevented transmission among health-care workers during the COVID-19 pandemic. During times of intense shortage of respirators and border closures during the pandemic, re-use strategies with available decontamination methods were necessitated. This in-house experimental study evaluated the effect of hydrogen peroxide gas-plasma sterilization on respirators and helped establish an evidence-based protocol for their re-use in a resource-poor setting. Materials and Methods: A three-dimensional experimental model using saline nebulization as the aerosol exposure and a particle counter to measure the filtration of particles through the mask pre- and post-sterilization was used. Multiple cycles of plasma sterilization were done till the physical integrity/fit was lost. Total filtration volume was used as a surrogate marker to assess the filtration efficiency (FE). Results: The total volume of particles filtered on a 3M respirator was 99.9%. Unused Halyard and Venus respirators were compared against 3M and found to have FE of 99.9% and 60.5%, respectively. After repeated sterilization cycles, the total volume of particles filtered was 59.3% for Halyard in the seventh cycle and 36.2% for Venus in the fifth cycle. When the physical integrity and fit was tested, the appropriate fit was lost after eight cycles of sterilization for Venus and was not lost for Halyard even after the tenth cycle. Conclusion: This low-cost experimental study helped implement an effective and safe decontamination strategy for safe re-use of N95 respirators in an emergent situation with no access to commercial testing in a resource poor health-care setting during the pandemic.